The impact of the alternative tax base measurement policy on the VAT revenue performance in the Indonesian agricultural sector - Singgih Priyogo; Rus'an Nasrudin (Scientax: Jurnal Kajian Ilmiah Perpajakan Indonesia, 2023)
Informality issues and government distributional objectives cause the need for VAT special treatment for the agricultural sector. The treatment forms and resulting impacts vary, depending on each country's conditions and necessities. This study aims to estimate the impact of the alternative tax base measurement policies on the VAT revenue performance in the Indonesian agricultural sector. Using input-output table modeling, the authors found that the policy positively impacts the compliance level and VAT revenue in the agricultural sector but reduces the aggregate national VAT revenues and increases the VAT burden that the agricultural sector entrepreneurs must bear. The normal VAT mechanism is preferred for the long-term goal, but the alternative policy is still needed during the transition period.